(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In excess of 150 countries have executed GST starting at as of late. It is a total tax framework that will subsume all roundabout taxes of states and central governments and joined economy into a solid national market. GST is a victor among the most fundamental tax changes in India which has been long pending in India. It is required to revive existing circuitous tax framework and expect an essential employment being developed of India. This paper presents an outline of SEZ and GST thought, clears up their features and application in India. The examination moreover fights the SEZs’ potential in India in pulling in speculation and propelling fares. As the new arrangement of GST for SEZs gives an imperative push to SEZs, the middle is in like manner over to grasp the impact of proposed GST organization over the advancement and enhancement of the country through SEZs. This examination shyly goes for investigating the impact of GST on Special Economic Zones (SEZs).